Validation of the continuous glucose monitoring sensor in preterm infants. Issue 2 (12th July 2012) - Beardsall, K; Vanhaesebrouck, S; Ogilvy-Stuart, A L; Vanhole, C; vanWeissenbruch, M; Midgley, P; Thio, M; Cornette, L; Ossuetta, I; Palmer, C R; Iglesias, I; de Jong, M; et al.
Abstract : Objective: Recent studies have highlighted the need for improved methods of monitoring glucose control in intensive care to reduce hyperglycaemia, without increasing the risk of hypoglycaemia. Continuous glucose monitoring is increasingly used in children with diabetes, but there are little data regarding its use in the preterm infant, particularly at extremes of glucose levels and over prolonged periods. This study aimed to assess the accuracy of the continuous glucose monitoring sensor (CGMS) across the glucose profile, and to determine whether there was any deterioration over a 7 day period. Design: Prospectively collected CGMS data from the NIRTURE Trial was compared with the data obtained simultaneously using point of care glucose monitors. Setting: An international multicentre randomised controlled trial. Patients: One hundred and eighty-eight very low birth weight control infants. Outcome measures: Optimal accuracy, performance goals (American Diabetes Association consensus), Bland Altman, Error Grid analyses and accuracy. Results: The mean (SD) duration of CGMS recordings was 156.18 (29) h (6.5 days), with a total of 5207 paired glucose levels. CGMS data correlated well with point of care devices (r=0.94), with minimal bias. It met the Clarke Error Grid and Consensus Grid criteria for clinical significance. Accuracy of single readings to detect set thresholds of hypoglycaemia, or hyperglycaemia was poor. There was no deterioration over time from insertion. Conclusions: CGMS can provide information on trends in glucose control, and guidance on the need for blood glucose assessment. This highlights the potential use of CGMS in optimising glucose control in preterm infants.